The Complete Adventures Of Feluda, Volume 2 - Satyajit Ray; Gopa Majumdar (Penguin , Haryana, 2015)
For readers who enjoyed the adventures of Feluda in Volume 1, this second omnibus volume holds more delights. Accompanied by his cousin Topshe and the bumbling crime writer Lalmohan Ganguly (Jatayu), Feluda travels from Puri to Kedarnath, from Kathmandu to London in his pursuit of culprits; he tracks down Napoleon's last letter, a forgotten painting by Tintoretto and a stolen manuscript.
Translated from the Bengali by Gopa Majumdar.
Keywords: Indian Fiction; Detective and mystery fiction; Action & Adventure